Salary service in Advance in Islamic banks An applied jurisprudence comparison study (Damascus University Journal for legal sciences, 2025)
The study aimed to clarify the meaning of salary, the meaning of Islamic banks, and to refer to the image of the salary provision service and how to apply it in Bank Nizwa, and to clarify the jurisprudential conditioning of the salary provision service, and to talk about its jurisprudential ruling, and to explain the jurisprudential conditioning of the salary provision service in the Omani Civil Transactions Law.The study included two sections, the first section dealt with a general definition of the research vocabulary, and the second section dealt with the legality of the salary provision service and its jurisprudential provisions.The study concluded that the jurisprudential and legal adaptation of the salary provision service in Islamic banks, including Bank Nizwa, is that it is a “KARDH HASAN” obtained by the customer from the bank, and the customer is obligated to return the same amount, description and quality upon the agreed term, despite the agreement of contemporary jurists on the jurisprudential adaptation of this service. However, they differed in its ruling, and the origin of the dispute is the commission that the customer pays to the bank in exchange for that service.The study recommended that Islamic banks, including Bank Nizwa, publish fatwas and decisions of the Sharia Supervisory Board. And that Bank Nizwa shall periodically study the costs incurred by it in order to provide this service; To ensure that the costs incurred are complied with without any increase in them.
Keywords: Islamic Banks; Salary Provision; Bank Nizwa; Sultanate Of Oman; Omani Law